Lithium alloy anode

By using surface tension reducing agents to wet the anode current collector in lithium metal batteries and forming lithium alloy anode, the problems of unreliable performance and short life of lithium metal batteries are solved, and more efficient manufacturing processes and longer battery life are achieved.

CN119695047APending Publication Date: 2025-03-25GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311567940.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2023-11-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Lithium metal batteries may exhibit unreliable performance and short life, mainly due to the weak long-term adhesion of lithium metal to metal current collectors, resulting in increased resistance and impedance over time.

Method used

By forming a melt including lithium and a surface tension reducing agent, the anode current collector is wetted to form a lithium alloy anode. The surface tension reducing agent is selected from silver, tin, gallium, indium, zinc and combinations thereof and is added to the molten lithium until the melt has a flat surface.

Benefits of technology

This method simplifies the manufacturing process, reduces costs, and improves the wettability of the lithium alloy anode and adhesion to the current collector, thereby extending the battery life and improving performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695047A_ABST
    Figure CN119695047A_ABST
Patent Text Reader

Abstract

A method for manufacturing an anode, a method for manufacturing a battery, and a lithium battery are disclosed. A method for manufacturing an anode includes forming a melt including lithium and a surface tension reducing agent, wherein the surface tension reducing agent is selected from the group consisting of silver, tin, gallium, indium, zinc, and combinations thereof; and contacting an anode current collector with the melt, wherein a layer of the melt is wetted onto the anode current collector to form an anode as a lithium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] FIELD OF THE DISCLOSURE The present disclosure relates generally to lithium anodes and methods for fabricating lithium anodes on current collectors to form lithium batteries. Background Art

[0002] High energy density electrochemical cells (such as lithium-ion batteries) can be used in various consumer products and vehicles, such as hybrid electric vehicles (HEV) and electric vehicles (EV). A typical lithium-ion battery includes a first electrode, a second electrode, an electrolyte material and a separator. One electrode is used as a positive electrode or cathode (when discharging), and the other is used as a negative electrode or anode (when discharging). A stack of battery cells can be electrically connected to increase the total output. Conventional rechargeable lithium-ion batteries operate by reversibly transferring lithium ions back and forth between the negative electrode and the positive electrode. The separator and electrolyte are disposed between the negative electrode and the positive electrode. The electrolyte is suitable for conducting lithium ions and can be in solid (e.g., solid state diffusion) or liquid form. Lithium ions move from the cathode (positive electrode) to the anode (negative electrode) during battery charging, and move in the opposite direction when discharging the battery.

[0003] The negative electrode (anode) can be made of metallic lithium, often referred to as a lithium metal anode (LMA), such that the electrochemical cell is considered a lithium metal battery or cell. Metallic lithium used for the negative electrode (anode) of a rechargeable battery has various potential advantages, including having the highest theoretical capacity and the lowest electrochemical potential. Therefore, a battery containing a lithium metal anode can have a higher energy density that can potentially double the storage capacity, so that the battery can be half the size but still last the same amount of time as other lithium-ion batteries. Therefore, lithium metal batteries are one of the most promising candidates for high energy storage systems.

[0004] However, lithium metal batteries may potentially exhibit unreliable or reduced performance, resulting in the possibility of shortened electrochemical cell life. For example, a potential source of reduced performance in lithium metal batteries may be related to the weak long-term adhesion of lithium metal to the metal current collector, which may lead to an undesirable increase in resistance and impedance over time when a lithium-based negative electrode is used in an electrochemical cell. Accordingly, it is desirable to develop reliable, high-performance lithium-containing negative electrode materials for high-energy electrochemical cells that can minimize the degradation of performance over time (e.g., minimize the increase in resistance / impedance and capacity decay due to long-term use). In addition, it is desirable to provide an improved method for manufacturing lithium-based anodes and lithium batteries using lithium-based anodes. Summary of the invention

[0005] In one embodiment, a method for making an anode includes: forming a melt including lithium and a surface tension reducer, wherein the surface tension reducer is selected from the group consisting of silver, tin, gallium, indium, zinc, and combinations thereof; and contacting an anode current collector with the melt, wherein a layer of the melt wets onto the anode current collector to form the anode being a lithium alloy.

[0006] In certain embodiments of the method, the layer of melt has a thickness from 30 to 60 micrometers (μm).

[0007] In certain embodiments of the method, the anode current collector is formed into a web of strips, and the layer of melt surrounds the strips.

[0008] In certain embodiments of the method, the anode current collector is copper or stainless steel.

[0009] In certain embodiments of the method, forming the melt includes melting solid lithium to form molten lithium; and adding a surface tension reducing agent to the molten lithium.

[0010] In certain embodiments of the method, forming the melt includes melting solid lithium to form molten lithium having a rounded surface; and adding a surface tension reducing agent to the molten lithium to form the melt.

[0011] In certain embodiments of the method, forming the melt includes melting solid lithium to form molten lithium having a rounded surface; and adding a surface tension reducing agent to the molten lithium until the melt has a flat surface.

[0012] In certain embodiments of the method, the surface tension reducing agent is silver and the lithium alloy is a lithium-silver alloy including less than 1 atomic % silver.

[0013] In certain embodiments of the method, the surface tension reducing agent is tin and the lithium alloy is a lithium-tin alloy including less than 10 atomic % tin.

[0014] In certain embodiments of the method, the surface tension reducing agent is gallium and the lithium alloy is a lithium-gallium alloy including less than 20 atomic % gallium.

[0015] In certain embodiments of the method, the surface tension reducing agent is indium and the lithium alloy is a lithium-indium alloy including less than 20 atomic % indium.

[0016] In certain embodiments of the method, the surface tension reducing agent is zinc and the lithium alloy is a lithium-zinc alloy including less than 30 atomic % zinc.

[0017] In an embodiment, a method for manufacturing a battery includes: wetting an anode current collector with a melt to form an anode that is a lithium alloy on the anode current collector, wherein the melt includes lithium and a surface tension reducer, and wherein the surface tension reducer is selected from the group consisting of silver, tin, gallium, indium, zinc, and combinations thereof; separating the anode from the cathode with a separator; and contacting the anode and the cathode with an electrolyte.

[0018] In certain embodiments, the method further includes forming the melt by melting solid lithium to form molten lithium, and adding a surface tension reducing agent to the molten lithium.

[0019] In certain embodiments, the method further includes forming the melt by melting solid lithium to form molten lithium having a rounded surface, and adding a surface tension reducing agent to the molten lithium until the melt has a flat surface.

[0020] In an embodiment, a lithium battery includes: an anode current collector formed from a current collector material; an anode active material directly contacting the current collector material, wherein the anode active material is a lithium alloy of lithium and silver, tin, gallium and / or indium; a cathode active material; a separator between the anode active material and the cathode active material; and an electrolyte in contact with the anode active material and the cathode active material.

[0021] In certain embodiments of the battery, the lithium alloy is a lithium-silver alloy including less than 1 atomic % silver.

[0022] In certain embodiments of the battery, the lithium alloy is a lithium-tin alloy including less than 10 atomic % tin.

[0023] In certain embodiments of the battery, the lithium alloy is a lithium-gallium alloy including less than 20 atomic % gallium.

[0024] In certain embodiments of the battery, the lithium alloy is a lithium-zinc alloy including less than 30 atomic % zinc.

[0025] In certain embodiments of the battery, the current collector material is copper or stainless steel.

[0026] In certain embodiments of the battery, the anode current collector is a mesh formed from strips of current collector material, and the mesh is surrounded by the anode active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present disclosure will be described below in conjunction with the following drawings, wherein like numerals designate like elements, and wherein:

[0028] Figure 1 is a schematic diagram of successive manufacturing stages of a method for manufacturing a lithium alloy metal anode according to an exemplary embodiment of the present disclosure;

[0029] Figure 2is a schematic diagram of a battery formed with a lithium alloy metal anode according to an embodiment of the present disclosure;

[0030] Figure 3 is a perspective view of a mesh current collector used in certain embodiments of the present disclosure;

[0031] Figure 4 is a cross-sectional view of a lithium alloy anode formed around a wire or strip of a mesh current collector according to an embodiment of the present disclosure;

[0032] Figure 5 is a schematic diagram illustrating contact angle, solid surface tension, liquid surface tension and solid / liquid interfacial tension; and

[0033] Figure 6 is a free energy composition diagram for a binary Li-X molten liquid as a function of the concentration of the alloying element X according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0034] The following detailed description is merely exemplary in nature and is not intended to limit the application and use of the embodiments herein. In addition, it is not intended to be bound by any express or implied theory presented in the aforementioned background technology, the invention content, or the detailed description below. As used herein, the term module refers to any hardware, software, firmware, electronic control unit or component, processing logic and / or processor device (alone or in any combination), including but not limited to: application-specific integrated circuits (ASICs), electronic circuits, processors (shared, dedicated or groups) and memories that execute one or more software or firmware programs, combinational logic circuits, and / or other suitable components that provide the described functions.

[0035] Embodiments of the present disclosure may be described herein in terms of functional and / or logical block components and various processing steps. It should be understood that such block components may be implemented by any number of hardware, software, and / or firmware components configured to perform specified functions. For example, embodiments of the present disclosure may employ various integrated circuit components, such as memory elements, digital signal processing elements, logic elements, lookup tables, etc., which may perform various functions under the control of one or more microprocessors or other control devices. In addition, those skilled in the art will appreciate that embodiments of the present disclosure may be practiced in conjunction with any number of autonomous driving systems (including cruise control systems, automatic driver assistance systems, and autonomous driving systems), and the vehicle system described herein is only an example embodiment of the present disclosure.

[0036] Finally, for the sake of brevity, conventional techniques and components related to other functional aspects of vehicle mechanical components and systems (and the individual operating components of the systems) may not be described in detail herein. In addition, the connecting lines shown in the various figures contained herein are intended to represent example functional relationships and / or physical couplings between the various elements. It should be noted that many alternative or additional functional relationships or physical connections may exist in the embodiments. It should also be understood that the drawings are merely illustrative and may not be drawn to scale.

[0037] In addition, the following description relates to elements or features being "connected" or "coupled" together. As used herein, "connection" may refer to an element / feature being directly engaged to another element / feature (or being directly communicated with it), and not necessarily mechanically. Similarly, "coupling" may refer to an element / feature being directly or indirectly engaged to another element / feature (or being directly or indirectly communicated with it), and not necessarily mechanically. However, it should be understood that although two elements can be described as being "connected" in one embodiment below, in alternative embodiments, similar elements can be "coupled", and vice versa. Therefore, although the schematic diagram shown herein depicts the example arrangement of elements, additional intermediary elements, devices, features or parts may be present in actual embodiments.

[0038] Exemplary lithium batteries, methods for making anodes, and methods for making batteries are provided to simplify the manufacturing process and reduce costs.

[0039] In certain embodiments, a lithium alloy bath having a reduced surface tension compared to a lithium bath is provided to allow lithium to spontaneously wet onto the current collector without requiring any lithium-philic coating or surface treatment on the current collector. Because no lithium-philic coating or surface treatment process is required, the process is simplified, the process time is reduced, and the cost is reduced.

[0040] In addition, the use of a lithium alloy bath allows the current collector to be immersed in a molten bath for wetting both sides or all sides of the current collector. The current collector can be in the form of a foil with two sides, or a three-dimensional mesh of a wire or strip that can be surrounded by a molten bath. Therefore, the lithium alloy can be inserted into the voids of the mesh current collector without the need for a lithium-philic pre-coating or surface pretreatment process. In addition, for the mesh current collector, the reduced surface tension of the molten alloy bath prevents excessive deformation of the mesh when it is inserted into or pulled out of the molten alloy bath.

[0041] In certain embodiments, the surface tension and wettability of the alloy bath on the current collector can be adjusted by controlling the addition of a surface tension reducer (or alloying element) to the molten lithium. The surface tension reducer can be selected from silver, tin, gallium, indium, zinc and combinations thereof. The surface tension reducer can be added to the bath until the surface shape of the bath changes. For example, the molten lithium bath has a convex meniscus shape. The meniscus shape can be used as an indicator to determine the appropriate amount of surface tension reducer added. Certain embodiments determine that when the meniscus is no longer convex, that is, when the upper surface of the bath is plane or flat, an appropriate amount of surface tension reducer has been added.

[0042] In addition, in some embodiments, the thickness of the lithium alloy anode material formed on or around the current collector can be adjusted by controlling the addition of a surface tension reducer (or alloying element) to the molten lithium. For example, the thickness of the lithium alloy anode material formed on or around the current collector can be from 30 to 60 microns (μm).

[0043] In certain embodiments, silver is added to a molten lithium bath such that the bath has a total silver content of less than 1 atomic percent. In certain embodiments, tin is added to a molten lithium bath such that the bath has a total tin content of less than 10 atomic percent. In certain embodiments, gallium is added to a molten lithium bath such that the bath has a total gallium content of less than 20 atomic percent. In certain embodiments, indium is added to a molten lithium bath such that the bath has a total indium content of less than 20 atomic percent. In certain embodiments, zinc is added to a molten lithium bath such that the bath has a total zinc content of less than 30 atomic percent.

[0044] In other embodiments, the anode may be formed as a lithium alloy foil. The lithium alloy foil may be rolled or otherwise formed.

[0045] Referring to the drawings, wherein like reference numerals refer to like parts, Figure 1 1 is a simplified schematic diagram of a method 10 for making an anode 100 suitable for use in a battery for powering a vehicle such as a pure electric vehicle or a hybrid electric vehicle. The vehicle can be any of a number of different types of automobiles, such as, for example, a sedan, van, truck, or sport utility vehicle (SUV).

[0046] As shown, method 10 includes providing lithium 50 in a container 40 at a manufacturing stage 11, such as in a solid form, such as particles or powder. The method also includes heating the container and lithium to melt the lithium at a manufacturing stage 12, thereby forming molten lithium 60, that is, a molten lithium bath 60. The molten lithium 60 has a high surface tension. Due to the high surface tension, the molten lithium bath 60 has a circular upper surface 65. Specifically, the upper surface 65 forms a convex meniscus, as shown. If provided in a larger container, the molten lithium bath 60 can form a spherical shape. It has been determined that the high surface tension of the molten lithium bath 60 prevents wetting onto a substrate (such as a copper or stainless steel substrate).

[0047] The method also includes adding a surface tension reducing agent or alloying element 70 to the molten lithium bath 60 to reduce the surface tension at the manufacturing stage 13. The surface tension reducing agent is selected from the group consisting of silver, tin, gallium, indium, zinc and combinations thereof. Suitable surface tension reducing agents melt at the temperature of the bath, exhibit solubility in the molten lithium, and form a binary liquid phase having a lower free energy than pure lithium.

[0048] The addition of the surface tension reducing agent or alloying element 70 to the molten lithium bath 60 produces a melt 80 having a reduced surface tension compared to the molten lithium bath. In an exemplary embodiment, the melt 80 may have a planar or flat upper surface 85. In practice, the presence or absence of a meniscus may be used to control the amount of the surface tension reducing agent 70 added to the molten lithium bath 60. In other words, when the flat upper surface 85 is formed, then enough surface tension reducing agent 70 has been added to the molten lithium bath 60. Thus, the method 10 may include stopping the addition of the surface tension reducing agent or alloying element 70 to the bath when a sufficient amount has been added, as shown in manufacturing stage 14.

[0049] In an exemplary embodiment, the surface tension reducing agent or alloying element 70 is silver and is added to the molten lithium bath 60 so that the melt 80 has a total silver content of less than 1 atomic percent (such as less than 0.9, 0.8, 0.7, 0.6, or 0.5 atomic percent). In an exemplary embodiment, the surface tension reducing agent or alloying element 70 is tin and is added to the molten lithium bath 60 so that the melt 80 has a total tin content of less than 10 atomic percent (such as less than 9, 8, 7, 6, 5, 4, 3, or 2 atomic percent). In an exemplary embodiment, the surface tension reducing agent or alloying element 70 is gallium and is added to the molten lithium bath 60 so that the melt 80 has a total gallium content of less than 20 atomic percent (such as less than 18, 16, 14, 12, 10, or 5 atomic percent). In an exemplary embodiment, the surface tension reducing agent or alloying element 70 is indium and is added to the molten lithium bath 60 so that the melt 80 has a total indium content of less than 20 atomic percent (such as less than 18, 16, 14, 12, 10, or 5 atomic percent). In an exemplary embodiment, the surface tension reducing agent or alloying element 70 is zinc and is added to the molten lithium bath 60 such that the melt 80 has a total zinc content of less than 30 atomic percent, such as less than 25, 20, 15, 12, 10, or 5 atomic percent. In an exemplary embodiment, the surface tension reducing agent or alloying element 70 is a combination of additives and is added to the molten lithium bath 60 such that the melt 80 has a total additive content of less than 40 atomic percent, such as less than 35, 32, 30, 25, 20, 15, 12, 10, or 5 atomic percent.

[0050] Therefore, the method provides for forming a melt 80 including lithium and a surface tension reducer, wherein the surface tension reducer is selected from the group consisting of silver, tin, gallium, indium, zinc and a combination thereof. After forming the melt 80 of lithium and the surface tension reducer, the method can continue to contact the anode current collector 110 with the melt 80, as shown in manufacturing stage 15. Therefore, the layer of melt 80 is wetted onto the anode current collector 110 to form the anode 100 as a lithium metal anode, and is specifically formed as a lithium alloy metal anode. The improved wetting provided by adding a surface tension reducer improves the adhesion of the lithium alloy active material to the current collector 110, thereby resulting in better performance and longer life of the anode and the battery. In certain embodiments, the current collector 110 is formed of copper or stainless steel. In certain embodiments, the current collector 110 can be formed of another suitable material.

[0051] In certain embodiments, the anode current collector 110 is immersed in the melt 80. For example, as shown, a portion of the anode current collector 110 may be immersed in the melt 80, or the entire anode current collector 110 may be immersed in the melt 80.

[0052] The method includes stopping the contact between the anode current collector 110 and the melt 80, as shown in manufacturing stage 16. For example, the anode current collector 110 can be removed from the bath and the container. As shown in the figure, the layer of melt 80 solidifies into an anode active material with a thickness of 105 on the current collector 110. The thickness is measured in the direction perpendicular to the surface of the current collector 110 (or perpendicular to the tangent of the curved surface of the current collector 110). In some embodiments, the thickness 105 of the solid layer is at least 5 microns (μm), such as at least 10, 15, 20, 25, 30, 35, 40, 45, 50 or 55 microns (μm). In some embodiments, the thickness 105 of the solid layer is no more than 80 microns (μm), such as no more than 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25 or 20 microns (μm).

[0053] like Figure 2 As shown, in some embodiments, the method continues to manufacture the battery 200. For example, the method may include wetting the anode current collector 110 with the melt 80 to form the anode 100 as a lithium alloy on the anode current collector 110. In addition, the method may include separating the anode 100 from the cathode 130 with the separator 120. In addition, the method may include contacting the anode 100 and the cathode 130 with the electrolyte 150.

[0054] Figure 1 and Figure 2 An anode current collector 110 is shown as a foil or solid substrate having two opposing surfaces 111 and 112. Figure 1 In the embodiment, the lithium alloy is formed on both surfaces 111 and 112. It is contemplated that the lithium alloy may be formed on only one surface 111.

[0055] In some embodiments, the anode current collector 110 is a mesh or other porous substrate. For example, Figure 3 A top view of an anode current collector 110 formed into a mesh 115 of interconnected wires or strips 116 defining open cells 118 is provided. When the mesh anode current collector 110 is contacted with the melt 80, the melt 80 surrounds the strips 116 and fills the open cells 118. Specifically, capillary forces may facilitate wicking of the melt 80 to diffuse across the anode current collector 110, such as into the cells 118.

[0056] Figure 4 The figure shows a cross-sectional view of the strip 116 and surrounding cells 118 of the mesh anode current collector 110 after contacting with the melt 80 to form the anode 100. As shown, the melt 80 fills the open cells 118 and surrounds the strip 116 such that the mesh is embedded in the anode 100. Although the strip 116 is shown to have a circular cross-section, it is contemplated that the strip 116 can be formed to have different shapes.

[0057] In addition, anode 100 has a maximum thickness 106, wherein the anode material extends continuously between opposing anode surfaces 107 and 108. In certain embodiments, thickness 106 is at least 5 micrometers (μm), such as at least 10, 15, 20, 25, 30, 35, 40, 45, 50, or 55 micrometers (μm). In certain embodiments, thickness 105 does not exceed 80 micrometers (μm), such as not more than 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, or 20 micrometers (μm).

[0058] Whether it is formed in Figure 1 and Figure 2 The foil current collector 110 is formed on the Figure 4 The solid metal anode 100 is a lithium alloy (LiX) on a mesh current collector 110 in the embodiment of the present invention, wherein X is one or more alloying elements 70. In certain embodiments, the lithium alloy has a lithium content of at least 70 atomic % lithium, such as at least 75, 78, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 99.1, 99.2, 99.3, 99.4, 99.5, 99.6, 99.7, 99.8 or 99.9 atomic % lithium.

[0059] As mentioned above, surface tension reducers or alloying elements 70 can be selected to reduce the surface tension of the bath before the current collector contacts the bath. Surface tension is a key parameter for determining the wetting of a surface (such as a current collector surface). Surface tension (γ) is generally defined as an unbalanced force (given in units of dyn / cm or mN / m) that works in a material to adapt to the smallest possible surface under set conditions. The appearance of these unbalanced forces is due to the cohesive force between molecules in the surface layer being not evenly distributed to all sides compared to molecules in the internal phase.

[0060] When the molten liquid contacts the current collector surface, surface tension acts to redistribute the molten liquid. If the surface tension of the molten liquid is higher than the surface tension of the substrate, the molten liquid will obtain the lowest possible common surface with the substrate. Therefore, the molten liquid will not be able to wet the surface properly, resulting in surface defects (bare spots on the current collector).

[0061] like Figure 5 As shown, the contact angle θ is the angle between the intersection of the liquid-solid interface and the liquid-gas interface at the three-phase contact line. It is an indicator of the ability of a liquid to spread on a substrate.

[0062] Solid / liquid (S / L) interfaces exhibit different "surface tensions" than individual surfaces. The relationship between S / L surface tensions can be derived from Young's equation:

[0063]

[0064] in:

[0065] γ S Represents the surface tension of the solid (current collector);

[0066] γ L It represents the surface tension of liquid (molten lithium or alloy);

[0067] γ SL represents the solid / liquid interfacial tension; and

[0068] θ is the contact angle.

[0069] Therefore, the interfacial tension γ SL can be determined by measuring the contact angle θ. If the contact angle θ is greater than zero and less than 90 degrees, partial wetting occurs; and when the contact angle θ is zero, spontaneous and complete wetting occurs, which means that γ S >γ L (The surface tension of solids is greater than that of liquids).

[0070] When the liquid is molten lithium 60, the surface tension γ L high and results in a high (obtuse) contact angle. Thus, a spherical ball shape can be obtained for pure molten lithium. The surface tension of the molten liquid γ L It can be reduced by adding alloying elements (X) that react with lithium and replace the Li-Li bonds at the liquid surface with more Li-X bonds.

[0071] It has been determined that alloying elements should be selected so that: (a) the alloying elements have solubility in lithium. Silver has a particularly high solubility in lithium. Solubility can be indicated as a maximum equilibrium solubility limit, which is expressed in atomic percentage (at.%). A value of 100 at.% indicates complete solubility, while a value of 0 at.% indicates immiscibility. In practice, the solubility of silver in liquid lithium is from about 22 at.% to about 35 at.%, based on the temperature of the molten lithium. For example, the solubility of silver in lithium is 22 at.% at a temperature of 180°C and 35 at.% at a temperature of 300°C.

[0072] In certain embodiments, the solubility of the alloying element in molten lithium at the process temperature can be at least 0.1 at.%, such as at least 0.5, 1, 2, 5, 10, 15, 20, 25, 30, or 35 at.%. In certain embodiments, the solubility of the alloying element in molten lithium at the process temperature can be at most 40 at.%, such as at most 35, 30, 25, 20, 15, 10, 5, 2, 1, or 0.5 at.%.

[0073] Furthermore, it has been determined that the alloying element X should be selected such that: (b) the Gibbs free energy of mixing is negative, ie, the Li-X system has a much less negative Gibbs free energy than the Li-Li system at the same temperature.

[0074] The relationship between contact angle and Gibbs free energy is shown in the following equation:

[0075]

[0076] in:

[0077] θ 1 is the contact angle of molten Li-X alloy;

[0078] θ 2 is the contact angle of molten lithium; and

[0079] ΔG is the change in Gibbs free energy caused by the addition of alloying element X to lithium.

[0080] Figure 6 is a free energy composition diagram for a binary Li-X molten liquid as a function of the concentration of the alloying element X. In this diagram, the horizontal axis is the mole fraction of the alloying element X in the liquid, and the vertical axis is the change in Gibbs free energy (ΔG) of the binary mixture compared to pure lithium. mix ), the change is measured in joules.

[0081] Line 601 represents the change in free energy of a lithium-silver (Li-Ag) molten liquid. Line 602 represents the change in free energy of a lithium-tin (Li-Sn) molten liquid. Line 603 represents the change in free energy of a lithium-gallium (Li-Ga) molten liquid. Line 604 represents the change in free energy of a lithium-zinc (Li-Zn) molten liquid. ΔG mix The negative value of indicates a spontaneous reaction between Li and element X. As a result, new Li-X bonds replace Li-Li bonds, thereby improving the wettability of the melt.

[0082] Note that the thickness of the lithium alloy (LiX) layer formed as the anode can increase with the increase of the absolute value of the free energy change. Specifically, the wetting of the melt on the current collector increases with the increase of the alloy addition in the bath, thereby causing a larger amount of lithium alloy (LiX) to be formed on the current collector. Therefore, the method herein can include adjusting the alloying elements added to the bath to control the anode thickness. In certain embodiments, the process is controlled to form an anode with a thickness of at least 10 microns (such as at least 15, 20, 25, 30, 40, 50, 60, 70, 80 or 90 microns). In certain embodiments, the process is controlled to form an anode with a thickness of at most 100 microns (such as at most 95, 90, 85, 80, 70, 60, 50, 40, 30, 20, 15 or 12 microns). Typically, the anode formed on the wire mesh current collector can have a larger thickness.

[0083] As described herein, the wettability of a lithium anode is improved by adding selected elements to form a binary molten liquid before contacting the liquid with a current collector. Thus, no additional lithiophilic coating or surface treatment is required on the current collector to induce spontaneous wetting. Thus, additional process steps are avoided.

[0084] Furthermore, the addition of selected elements to the molten lithium can prevent copper from dissolving from the copper current collector into the molten bath via chemical attack.

[0085] Accordingly, the embodiments herein provide improved wetting of the current collector with molten lithium anode material by adding a surface tension reducer in the form of alloying elements to lithium. Therefore, the current collector does not need to be coated or surface treated before contacting the anode material melt. When the anode material melt contacts the current collector, the molten alloy wets and forms a layer on the current collector. In this way, a lithium-containing anode is efficiently formed on the current collector. The embodiments herein provide controlled addition of specific alloying elements (Ag, Ga, In, Zn) to molten lithium. This is a cost-effective method for modifying the surface tension of molten lithium, and avoids the additional step of pre-treating the current collector surface to provide a lithium-philic coating.

[0086] Although at least one exemplary embodiment has been presented in the foregoing summary and detailed description, it should be understood that there are a large number of variations. It should also be understood that one or more exemplary embodiments are merely examples and are not intended to limit the scope, applicability, or configuration of the present disclosure in any way. Specifically, the foregoing summary and detailed description will provide a convenient roadmap for implementing one or more exemplary embodiments to those skilled in the art. It should be understood that various changes may be made to the functions and arrangements of the elements without departing from the scope of the present disclosure as set forth in the attached claims and their legal equivalents.

Claims

1. A method for manufacturing an anode, the method comprising: forming a melt comprising lithium and a surface tension reducing agent, wherein the surface tension reducing agent is selected from the group consisting of silver, tin, gallium, indium, zinc, and combinations thereof; and An anode current collector is contacted with the melt, wherein a layer of the melt wets onto the anode current collector to form the anode as a lithium alloy. 2 . The method of claim 1 , wherein the layer of the melt has a thickness of from 30 to 60 micrometers (μm). 3 . The method of claim 1 , wherein the anode current collector is formed into a web of strips, and wherein the layer of the melt surrounds the strips.

4. The method of claim 1 , wherein forming the melt comprises: melting solid lithium to form molten lithium; as well as The surface tension reducing agent is added to the molten lithium.

5. The method of claim 1 , wherein forming the melt comprises: melting solid lithium to form molten lithium having a rounded surface; as well as The surface tension reducing agent is added to the molten lithium to form the melt.

6. The method of claim 1 , wherein forming the melt comprises: melting solid lithium to form molten lithium having a rounded surface; as well as The surface tension reducing agent is added to the molten lithium until the melt has a flat surface.

7. The method according to claim 1, wherein: The surface tension reducing agent is silver, and the lithium alloy is a lithium-silver alloy including less than 1 atomic % silver; The surface tension reducing agent is tin, and the lithium alloy is a lithium-tin alloy including less than 10 atomic % tin; The surface tension reducing agent is gallium, and the lithium alloy is a lithium-gallium alloy including less than 20 atomic % gallium; The surface tension reducing agent is indium, and the lithium alloy is a lithium-indium alloy including less than 20 atomic % indium; or The surface tension reducing agent is zinc, and the lithium alloy is a lithium-zinc alloy including less than 30 atomic % zinc.

8. A lithium battery comprising: an anode current collector formed of a current collector material; an anode active material in direct contact with the current collector material, wherein the anode active material is a lithium alloy of lithium and silver, tin, gallium, indium and / or zinc; cathode active material; a separator between the anode active material and the cathode active material; as well as An electrolyte is in contact with the anode active material and the cathode active material.

9. The lithium battery according to claim 8, wherein: The lithium alloy is a lithium-silver alloy including less than 1 atomic % of silver; The lithium alloy is a lithium-tin alloy including less than 10 atomic % tin; The lithium alloy is a lithium-gallium alloy including less than 20 atomic % gallium; The lithium alloy is a lithium-indium alloy comprising less than 20 atomic % indium; or The lithium alloy is a lithium-zinc alloy including less than 30 atomic % zinc.

10. The lithium battery of claim 8, wherein the anode current collector is a mesh formed from strips of the current collector material, and wherein the mesh is surrounded by the anode active material.